Design gene based secure mechanism for collaborative product development. (January 2021) - Cai, X.T.; Wang, S.
Abstract: In collaborative product development, a CAD model needs to be effectively shared among partners to facilitate co-design. In the meantime, it is essential to preserve the intellectual property information (design knowledge) of the shared CAD. To resolve the above dilemma, this paper presents a novel approach to share CAD models to support collaboration, as well as conserving confidential design knowledge in the models. The motivation of the approach is to develop collaborative mechanisms pertaining to an innovative concept of design genes, which imitate biological genes that are responsible for the heritable characteristics of an organism during evolving. The approach consists of the following steps. Firstly, design genes are defined to represent the design knowledge in CAD models. Secondly, a filter is introduced to retrieve design genes from the CAD model flexibly. An encryption algorithm is then designed to encrypt the design genes, and ensure the geometrical validity of the model to support effective collaboration. Finally, case studies are used to validate the developed approach. The complexity of the case studies can demonstrate that the approach is applicable to real-world application scenarios.